2.79-μm high peak power LiNbO3 acousto-optic Q-switched Er,Cr:YSGG laser with thermal lensing effect compensation - Jiang, Lingling; Wu, Zhongchao; Ma, Shengjie; Zhu, Yongbin; Cheng, Tingqing; Jiang, Haihe (Frontiers in Physics, 2023)
A new type of lithium niobate (LiNbO3) acousto-optic Q-switched Er,Cr:YSGG laser with high peak power was designed and the thermal lensing effect compensation was studied. The values of thermal focal length in the gain medium were calculated theoretically and measured experimentally. The experimental results validate the designed plane-convex resonator validity, and the output performance of the 2.79 μm Er,Cr:YSGG laser was obviously improved. When the laser operated at free running region, the maximum values of pulse energy was 160 mJ at 60 Hz, compared with the plane-parallel resonator, the pulse energy was increased by 2 times in the plane-convex resonator. When the LiNbO3 Q-switched laser operated at 60 Hz, the maximum values of pulse energy was 8.5 mJ, and the minimum values of pulse duration was 60.8 ns, and the corresponding peak power approximately was 140 kW, respectively. Compared with the plane-parallel resonator, the pulse energy was increased by 1.6 times in the plane-convex resonator, the corresponding peak power was increased by 2.3 times.